Architectural - STP & WTP basement-2 layout and detail (RFA-139_Rev D) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.